Chemopreventive Potential of Raw and Roasted Pistachios Regarding Colon Carcinogenesis - Glei, Michael (Nutrients, 2017)
Pistachios are rich in health-promoting bioactive compounds such as B vitamins, γ-tocopherol, polyphenols and dietary fiber, which could contribute to the reduction of colon cancer risk in terms of chemoprevention (Fischer, S.; Glei, M. Health-Potential of Nuts. Ernaehrungs Umsch. Int. 2013, 60, 206–215.). Since pistachios are often consumed roasted, the present study aims at investigating the influence of different roasting conditions (RC) on potential chemopreventive effects of pistachios in colon adenoma cells such as growth and apoptosis, genotoxic- and anti-genotoxic effects and modulation of gene expression of detoxifying enzymes (CAT, SOD2, GPx1, and GSTP1). Fermentation supernatants (FS) were obtained from raw and roasted (RC1 = 141 °C/25 min, RC2 = 160 °C/15 min and RC3 = 185 °C/21 min) pistachios after in vitro fermentation. FS of pistachios significantly reduced LT97 cell growth in a time- and dose-dependent manner. Compared to the blank control, pistachio FS (2.5%) led to a significant average reduction of H(2)O(2)-induced DNA damage (1.5-fold). Levels of CAT mRNA were significantly increased (1.3-fold, on average for 5% FS). Pistachio FS (5%) significantly increased the number of early apoptotic cells (up to 2.1-fold) and levels of caspase-3 activities (up to 6.9-fold). The present results confirm a chemopreventive potential of pistachios, which is mediated by growth inhibition, induction of apoptosis and anti-genotoxic effects, as well as induction of CAT. These effects remain mostly unaffected by roasting.